2014
DOI: 10.1136/bjsports-2014-093842
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychological readiness to return to sport and recreational activities after anterior cruciate ligament reconstruction

Abstract: Background This cross-sectional study aimed to examine whether appraisal of knee function, psychological and demographic factors were related to returning to the preinjury sport and recreational activity following anterior cruciate ligament (ACL) reconstruction. Method 164 participants completed a questionnaire battery at 1-7 years after primary ACL reconstruction. The battery included questionnaires evaluating knee self-efficacy, health locus of control, psychological readiness to return to sport and recreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
355
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(379 citation statements)
references
References 44 publications
(54 reference statements)
15
355
2
7
Order By: Relevance
“…32 People choose to participate or cease participating for many reasons that may have nothing to do with their knee. 37 People may also change their sports participation following surgery on the advice of their treating clinician. These reasons may help to explain relationships between sports participation and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…32 People choose to participate or cease participating for many reasons that may have nothing to do with their knee. 37 People may also change their sports participation following surgery on the advice of their treating clinician. These reasons may help to explain relationships between sports participation and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found associations between return to sports and psychosocial/psychological variables (kinesiophobia/fear of reinjury, knee-related self-efficacy, confidence). 2,4,5,15,22,35,36 Further evaluation of the impact of these factors, along with that of strength, function, and performance, on return to sports is warranted. Third, only one criterion value (90%) was evaluated in this study, based on what is commonly regarded as acceptable for return-to-sport participation after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Of concern is that more than 50% of non-elite sports participants do not return to pre-injury sport after ACLR (Ardern et al, 2014b), which was a critical determinant of longer-term QOL 5 to 20 years after ACLR in people with knee difficulties (Chapter 6). Prior to this research, only two studies had explored the relationship between return to sport and QOL outcomes (Ardern et al, 2014a;McCullough et al, 2012). One study reported lower KOOS-QOL scores in high school and college athletes who did not return to sport compared to those who returned to their pre-injury level of sport two years after ACLR (McCullough et al, 2012).…”
Section: Return To Sportmentioning
confidence: 99%
“…Furthermore, emotional disturbances were reported by individuals who had not returned to sport at 6 and 12 months after ACLR, compared to those who had returned to sport, despite no differences in knee function and symptoms (Langford et al, 2009). Fear of re-injury is a very common psychological manifestation experienced by individuals after ACLR (Ardern et al, 2014a;Gignac et al, 2015;Kvist et al, 2005;Tripp et al, 2007) and higher levels of fear of re-injury have been associated with worse knee-related QOL (Kvist et al, 2005). Additionally, psychological factors assessed prior to undergoing ACLR are predictive of postoperative outcomes (Everhart, Best, & Flanigan, 2015).…”
Section: Psychological Outcomesmentioning
confidence: 99%
See 1 more Smart Citation